2020
DOI: 10.1155/2020/3272681
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Study on Dynamic Resilient Modulus of Lime‐Treated Expansive Soil

Abstract: Dynamic resilient modulus is the design index of highway subgrade design code in China, which is significantly affected by the traffic loads and environmental changes. In this study, dynamic triaxial tests were conducted to investigate the influence of moisture content, compaction degree, cyclic deviator stress, and confining pressure on lime-treated expansive soil. The suitability of UT-Austin model to lime-treated expansive soils was verified. The results indicate that the dynamic resilient modulus of lime-t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 35 publications
1
4
0
Order By: Relevance
“…The reduction is significant up to deviator stress of 41.4 kPa; beyond this the M R value is stable and reaches a constant value. This is attributed to the strain-softening behavior at low axial stress; similar observations were made by Atkinson [53], Zhang et al [54], Lu et al [55]. Strain-softening is due to load-induced damages on the structure of fine-grained soils when subjected to successive deviator stresses.…”
Section: Effect Of Lime-treatment and Fiber-reinforcement On Resilient Modulussupporting
confidence: 71%
“…The reduction is significant up to deviator stress of 41.4 kPa; beyond this the M R value is stable and reaches a constant value. This is attributed to the strain-softening behavior at low axial stress; similar observations were made by Atkinson [53], Zhang et al [54], Lu et al [55]. Strain-softening is due to load-induced damages on the structure of fine-grained soils when subjected to successive deviator stresses.…”
Section: Effect Of Lime-treatment and Fiber-reinforcement On Resilient Modulussupporting
confidence: 71%
“…The static and dynamic elastic modulus test data of NFLS are fitted to establish the variation relationship of them, as shown in Figure 12. The static and dynamic elastic modulus of NLS, FLS, and NFLS conforms to the linear, exponential, and logarithmic relations respectively, and the fitting formula is shown in Equations ( 15)- (17). From the comparison of static and dynamic elastic modulus prediction models according to Figure 11, it can be found that the change trend between the static and dynamic elastic modulus of NFLS and the content of nano clay and polypropylene fiber is basically the same.…”
Section: Relationship Between Static and Dynamic Elastic Modulusmentioning
confidence: 68%
“…Lu et al [16] studied the effects of moisture content, compactness, cyclic deviatoric stress, and confining pressure on the dynamic elastic modulus of lime treated expansive soil by using dynamic triaxial test, and verified the applicability of UT Austin model. Zhao et al [17] measured the stress-strain curve of solidified soft soil under different lime content and confining pressure through dynamic triaxial test, and analyzed the relationship between dynamic and static strength and the influence of lime content on dynamic strength. Therefore, fiber materials and nano materials play a positive role in the mechanical properties of modified LS.…”
Section: Introductionmentioning
confidence: 99%
“…Notably, previous studies indicate that the load response behavior of coarse and fine aggregates is stress-level dependent, suggesting the necessity of non-linear analysis for accurate pavement assessment [36][37][38][39][40][41][42]. Additional research underscores the influence of confining and deviatoric stress levels on the behavior of chemically stabilized soils [32,[43][44][45][46][47].…”
Section: Modeling and Non-linear Analysismentioning
confidence: 99%